Developing COVID-19 vaccine recommendations during the pandemic: The experience of Serbia's Expert Committee on Immunization - Markovic-Denic, Ljiljana; Popadic, Dusan; Jovanovic, Tanja; Bonaci-Nikolic, Branka; Samardzic, Janko; Tomic Spiric, Vesna; Rancic, Miljan; Sankar Datta, Siddhartha; Mosina, Liudmila; Jancic, Jasna; Vukomanovic, Goran; Jovanovic, Verica; et al. (Frontiers in Public Health, 2022)
A National Immunization Technical Advisory Group (NITAG) is a multi-disciplinary body of national experts that provide evidence-based recommendations to policy-makers to assist them in making informed immunization policy and programme decisions. During the COVID-19 pandemic, NITAGs faced many challenges in making evidence-based recommendations for COVID-19 vaccines due to the rapidly evolving situation with new vaccine products available in a short time period and limited data on vaccine effectiveness. The authors reviewed the process used by Serbia’s NITAG, which is called the Serbian expert committee, to develop COVID-19 vaccine recommendations during the COVID-19 pandemic. The article examines the challenges and successes faced by the committee. Serbia’s expert committee used the best available evidence to develop over forty recommendations on all aspects of COVID-19 vaccination. These expert committee recommendations facilitated the early procurement and successful roll-out of COVID-19 vaccines, guidance for vaccination of individuals at the highest risk, and high COVID-19 vaccination coverage in the country. The availability of five COVID-19 vaccines in Serbia was an advantage for the successful roll-out but posed challenges for the expert committee. Serbia’s expert committee plans to use the experience and best practices developed during the pandemic to improve and expand its work moving forward.